Development and Experiments of Low Frequency Ultrasonic Electrostatic Atomizing Nozzle with Double Resonators - Gao, Jianmin; Xu, Ke; He, Rui; Chen, Xiangchao; Tunio, Mazhar Hussain (International Journal of Agricultural and Biological Engineering, 2022)
Fine droplets with high adhesion can greatly improve the efficiency of atomization culture. Therefore, the development of a spray nozzle that can produce fine fog droplets with high adhesion is of great significance for aeroponics. Compared to piezoelectric ultrasonic atomizer, Hartmann resonator low-frequency ultrasonic electrostatic atomizer has the advantages of large atomization volume and constant liquid chemical structure, but the droplet size is larger. High-speed gas can generate low-frequency ultrasonic vibration sound waves in Hartmann resonator. The frequency and intensity of sound waves determine the atomization performance of supersonic atomizer nozzle. However, very few research literatures can be found on how the structure and operating parameters of Hartmann resonator affect the atomization performance. In order to improve the atomization performance of ultrasonic atomizer, a two-stage Hartmann resonator low-frequency ultrasonic electrostatic atomizer was designed. The shrinkage-type Laval tube was designed by fluid mechanics theory, and the design results were verified by fluent software. The virtual orthogonal test method was used to optimize the structure parameters of two-stage resonator and spray test was carried out. The results showed that when the included angle between the two stage resonators was 80, the diameter was 4.86 mm, the tube length ratio was 1.0 and the gas pressure was 0.5 MPa, the droplet size could reach 22.05 μm. Additionally, compared with the traditional Hartmann cavity with 90° included angle, the droplet size was decreased by 63%. The annular electrode was used as the charging electrode, and Comsol Multiphysics software was used to simulate and calculate the deformation and crushing process of electrostatic droplets and the influence of different voltage, surface tension and droplet diameter on the droplet deformation rate. The results showed that: (1) the optimum charge range of the electrode ring was within 20 mm of the axial distance along the electrode ring. (2) The higher the voltage U, the smaller the surface tension σ; the larger the droplet diameter d and the larger the droplet deformation rate. (3) The experimental results showed that the droplet size was inversely proportional to the gas pressure P0, electrostatic voltage U and spray height h. When the gas pressure and electrostatic voltage were 0.4 MPa and 18 kV, 0.4 MPa and 18 kV, respectively, the droplet sizes were 7.8 μm and 43.9 μm respectively, the droplet size difference between the two conditions was 82.2%. Keywords: ultrasonic atomization, Laval tube, two-stage resonance tube, electrostatic spray, deformation rupture, simulation analysis DOI: 10.25165/j.ijabe.20221504.6251 Citation: Jianmin Gao, Ke Xu, Rui He, Xiangchao Chen, Mazhar Hussain Tunio. Development and experiments of low frequency ultrasonic electrostatic atomizing nozzle with double resonators. Int J Agric & Biol Eng, 2022; 15(4): 39–48.